Leistenbeschwerden - Biedert, R. M. (Sport-Orthopädie - Sport-Traumatologie, 2011)
Groin pain is a common and disabling problem incurred by many athletes. Different anatomic structures can be involved, alone or in combination. The differential diagnosis of inguinal and groin problems includes up to 30 specific conditions. History and physical examination are most important for the initial diagnosis. Different imaging modalities and additional examinations are helpful to confirm the final diagnosis. This determines the necessary treatment. The obturator nerve entrapment is a rare problem in athletes suffering from groin pain and therefore the diagnosis is often missed leading to chronic complaints. Surgical obturator neurolysis can resolve the problem.